Exploring the best evidence research to design and implement social story interventions: A critically appraised topic. Issue 4 (2nd October 2021) - Johnston, Susan S.; Thompson, Robyn; Blue, Cheri W.; Reichle, Joe
Abstract: A critically appraised topic (CAT) is a rapid review that can be particularly useful for informing research and practice. The purpose of this CAT was twofold and was conducted to (a) examine the similarities and differences in the design and implementation of best evidence social story (SS) intervention research, and (b) determine whether there are common empirically validated intervention strategies embedded within SS intervention packages that may contribute to effectiveness. Evidence from this CAT suggests that SS interventions can effectively increase desired social and academic behaviors and decrease disruptive behaviors. Further, although similarities were identified, differences in the design and implementation of SS interventions were noted, and empirically validated intervention strategies embedded within SS intervention packages that may be contributing to effectiveness were detected. Variations in the design and implementation of SS interventions are discussed with regard to implications for practice and research. The authors propose an update to this CAT in November 2024.